Mesh–free Ventral Rectopexy for Women with Complete Rectal and Uterovaginal Prolapse - Tade, Adedayo O. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Mesh rectopexy may be associated with infective complications, erosion into the vagina or rectum, and disintegration or dislodgement. A mesh-free rectopexy will avoid these complications. Objective of the study was to perform mesh-free ventral rectopexy and assess its safety and effectiveness. MATERIALS AND METHODS: Nine women with complete rectal and uterovaginal prolapse were treated with total abdominal hysterectomy, closure of the vaginal vault, extirpation of the pouch of Douglas and suture of anterior rectal wall to the posterior vaginal wall (ventral suture rectopexy). The ventral suture rectopexy was achieved by three pairs of interrupted silk sutures, 2.5 cm above each other, and the first pair very close to the pelvic floor. This composite structure (anterior rectal wall and posterior vaginal wall), sits astride the perineal body. Intussusception and subsequent prolapse of the sutured rectum and vaginal wall is prevented. Vaginal vault prolapse was prevented by the suture of each round ligament of the uterus to the corresponding lateral vaginal fornix. No mesh was used. RESULTS: Nine multiparous women aged between 52 and 70 years had the procedure. The mean operative time was 135 minutes (range 110-220). The follow-up period was between 29 months and 7 years. Full continence was restored in all patients within eight weeks of the operation. Bowel habit returned to once daily in four patients and once every other day in the remaining five patients, within thirteen weeks of surgery. One patient had intermittent mucus discharge per rectum for six months. This stopped without a specific treatment. There has been no known recurrence in these nine patients. One patient developed wound infection as a complication. There was no mortality. All the patients are now asymptomatic. CONCLUSION: Ventral suture rectopexy is a safe and effective treatment for complete rectal prolapse in a selected group of patients.